Rent-Seeking, Political Budget Cycle, and Audit Opinion: An Analysis of Local Government Spending in Indonesia - Bangun Indra Permadi (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
Rent-seeking behavior is one factor associated with the poor performance of local governments in Indonesia. It is an opportunistic behavior that often occurs in the government's budget allocating process. This study aims to estimate rent-seeking size in regional governments in Indonesia based on Katz and Rosenberg's (1989) method. The determining factors used are the availability of resources and political events. In addition, as an expected control mechanism that may dampen rent-seeking size, auditing is introduced. Using the Generalized Least Square Regression method, this study employs a cross-section time-series panel dataset of 305 local governments from 2015 to 2019. There were three findings in this study: (1) there was a decreasing trend in rent-seeking size after the national election was held in 2014-2015; (2) local governments that held elections showed a tendency to have a higher degree of rent-seeking, especially when the current executives or "incumbents" were standing for election; and (3) local governments that received 'Unqualified Opinion' for their financial statements had a smaller size and allocations of the rents. Those might suggest that auditing was an effective governance mechanism to restrain opportunistic rent-seeking behavior.